Evaluation of local B1 field as dosimeter of RF heating for implant in MRI. Issue 6 (1st March 2019) - Wan, Sen; Jiang, Changqing; Ding, Jianqi; Li, Luming
Abstract : Radio frequency (RF) heating is a serious risk for a patient with an elongated implant during MRI scan. The conventional dosimeter of specific absorption rate (SAR) and the recently proposed B 1+rms may not accurately indicate the implant heating. The local B 1 field around the tip of a lead and its relationship with the RF heating were studied by numerical simulations. It was found that regardless of the route of the lead, the angle or position of placement, there was a strong linear correlation between the averaged square of local B 1 field and the rise in temperature. The evaluation range had an effect on the linearity. Generally, the local B 1 field performed better as a dosimeter of RF heating than SAR or B 1+rms at the isocentre.